Technology overuse Influencing Emerging Psychological Acquaintances among Youth - Khan, Gull-e-laala; Jamshaid, Amber; Hussain, Yasir; Zaheer, Hamna; Aamna Mukhtar (Journal of Social Sciences and Management Studies, 2024)
Family foundation is one of the main institutions prevailing since ages in all human communities. The main building block organization of developed societies are reverential families. To meet economic stability, social and emotional needs, family holds fundamental importance. Technological innovations as a cardinal principle have positioned a huge gap among intra-family relationships. Therefore, the current research emphasizes impact of modern electronic media creating psychological breaches among families in Pakistan. Phenomenological analysis in present research revealed that digital platforms impact negatively eradicating traditional family norms, values and ethical bonding by minimizing positive constructive interaction among family members for healthy upbringing. Data analysis in present research disclosed that digital platforms impact negatively eradicating traditional family norms, values and ethical bonding by minimizing positive constructive interaction among family members for healthy upbringing. In the collective scientific monogram, the influence of digitalization on family ties is not neglectable. It is pertinent to clarify that adulthood transitions rely on strong family bonding as families often hold prominent role in young-adult lives. Despite hindrances, electronic interruption among family bonding impacts deleteriously. To overcome future destructions, preemptive actions are quite necessary in terms of communal strategies, civic tutelage and healthcare.